2021
DOI: 10.3389/fpubh.2021.753447
|View full text |Cite
|
Sign up to set email alerts
|

Value and Cost Savings From Access to Multi-disciplinary Rehabilitation Services After Severe Acquired Brain Injury

Abstract: Acquired brain injury (ABI) is a major global public health problem and source of disability. A major contributor to disability after severe ABI is limited access to multidisciplinary rehabilitation, despite evidence of sustained functional gains, improved quality of life, increased return-to-work, and reduced need for long-term care. A societal model of value in rehabilitation matches patient and family expectations of outcomes and system expectations of value for money. A policy analysis of seven studies (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In addition to these outcomes, the integration of Linkworker or NeuroResource Facilitator into multidisciplinary team meetings has been noted to facilitate comprehensive assessments and connections to other services ( 52 – 54 ). It is noteworthy that the benefit of multidisciplinary teams has also been identified in research with individuals with TBI ( 89 , 90 ) or underserved populations, specifically in tailoring interventions to accommodate for TBI impairments ( 75 , 76 , 91 ). As such, opportunities to integrate linkage programs or services within the broader CJS context should be explored, particularly those that address the noted barriers regarding the cost and resources required to implement linkage programs ( 52 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these outcomes, the integration of Linkworker or NeuroResource Facilitator into multidisciplinary team meetings has been noted to facilitate comprehensive assessments and connections to other services ( 52 – 54 ). It is noteworthy that the benefit of multidisciplinary teams has also been identified in research with individuals with TBI ( 89 , 90 ) or underserved populations, specifically in tailoring interventions to accommodate for TBI impairments ( 75 , 76 , 91 ). As such, opportunities to integrate linkage programs or services within the broader CJS context should be explored, particularly those that address the noted barriers regarding the cost and resources required to implement linkage programs ( 52 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that we are unable to comment on the effectiveness of the multidisciplinary rehabilitation programs or interventions identified in this review due to potential biases identified during the quality appraisal, including but not limited to selection, reporting, and publication bias. However, multidisciplinary rehabilitation has been demonstrated to result in improved outcomes post-TBI and cost-related savings for the individuals and society (68)(69)(70)(71). As such, utilizing multidisciplinary teams to screen for TBI, conduct functional and cognitive assessments, and adapt programs and/or interventions to accommodate TBI-related impairments should be explored and its impact on outcomes assessed.…”
Section: Opportunities To Adapt Existing Rehabilitation For Individua...mentioning
confidence: 99%
“…Тяжелые социальные последствия инсульта и большие экономические затраты побуждают медицинское сообщество к совершенствованию мер профилактики и лечения острого нарушения мозгового кровообращения [1,2], реабилитационных подходов [3][4][5] и прогнозирования последствий острой мозговой катастрофы [6][7][8]. Высокое систолическое артериальное давление (САД) является одним из основных модифицированных факторов риска инсульта, обусловливающих его тяжесть [9][10][11].…”
Section: Introductionunclassified